Hypoferraemia during the early inflammatory response is dependent on tumour necrosis factor activity in a murine model of protracted peritonitis - Schubert, Thomas E. O.; Bosserhoff, Anja K.; Peyssonnaux, Carole; Echtenacher, Bernd; Knutson, Mitchell; Hofstaedter, Ferdinand; Maennel, Daniela N. (Molecular Medicine Reports, 2012)
On the grounds of clinical, in vitro and in vivo studies, tumour necrosis factor (TNF) is considered to be one of the inflammatory cytokines that contributes to to the generation of hypoferraemia and anaemia of inflammation (AI). We used a recently described murine model for AI and hypoferraemia, based on sublethal caecal ligation and puncture (CLP) with ensuing protracted peritonitis, to investigate the contribution of TNF to the generation of hypoferraemia. During the early inflammatory response to CLP, a marked decrease in serum iron concentration occurs within 8 h. To determine whether TNF contributes to the generation of hypoferraemia at this time point, we studied TNF-deficient mice and wild-type mice that underwent CLP. The serum iron concentration was decreased in wild-type mice whereas TNF-deficient mice maintained normal serum iron levels following CLP. Hypoferraemia in wild-type mice was accompanied by the downregulation of ferroportin 1 (Fp1) in macrophages. In the macrophages of TNF-deficient mice, Fp1 was not downregulated following CLP. The initial expression of hepcidin was detectable at the mRNA level but not at the protein level by immunohistochemistry in wild-type and TNF-deficient mice. Therefore, hepcidin does not appear to be involved in the regulation of early hypoferraemia. TNF appears to regulate the expression of Fp1 by transcriptional control. Our results demonstrate that TNF mediates hypoferraemia during the early inflammatory response by regulating the expression of Fp1 in macrophages.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Blood; Hypoferraemia; Mouse; Septic peritonitis; TNF